Studi Fenomenologi Pengalaman Pasien Penyakit Ginjal Kronik dalam Menjalani Hemodialisis - Risa Nurhayati; Sri Wahyuni; Bayhakki Bayhakki; Nurul Huda; Erika Erika (Universitas Pahlawan Tuanku Tambusai, 2026)
Introduction: Each patient has a different experience undergoing hemodialysis, depending on individual perceptions, social support, and self-care abilities. This study aims to explore the experiences of chronic kidney disease patients undergoing hemodialysis. Methods: This is a qualitative study with a phenomenological approach. The researcher used a purposive sampling technique to select eight informants for the participants, and analyzed using Colaizzi thematic analysis. Data validity was tested to increase trustworthiness through triangulation, member checking, dependability, confirmability, and transferability. Results: This study yielded three themes: 1) initial response to hemodialysis, 2) the process of accepting hemodialysis, and 3) motivation for regular hemodialysis. Conclusion: Nurses need to actively introduce coping strategies, involve families, and integrate medical and psychological aspects to support patient compliance and resilience